Factors affecting hydrolysis of polyvinyl acetate to polyvinyl alcohol. Issue 5 (October 2019) - Aruldass, S.; Mathivanan, V.; Mohamed, A.R.; Tye, C.T.
Abstract: This study provides additional insight into the effects of different operating parameters on the degree of hydrolysis of PVA with the presence of sodium hydroxide.